A Comparative Evaluation of the Mechanical Properties of Two Calcium Phosphate/Collagen Composite Materials and Their Osteogenic Effects on Adipose-Derived Stem Cells - Qing Li; Tong Wang; Gui-feng Zhang; Xin Yu; Jing Zhang; Gang Zhou; Zhi-hui Tang (Stem Cells International)
Adipose-derived stem cells (ADSCs) are ideal seed cells for use in bone tissue engineering and they have many advantages over other stem cells. In this study, two kinds of calcium phosphate/collagen composite scaffolds were prepared and their effects on the proliferation and osteogenic differentiation of ADSCs were investigated. The hydroxyapatite/β-tricalcium phosphate (HA/β-TCP) composite scaffolds (HTPSs), which have an additional β-tricalcium phosphate, resulted in better proliferation of ADSCs and showed osteogenesis-promoting effects. Therefore, such composite scaffolds, in combination with ADSCs or on their own, would be promising for use in bone regeneration and potential clinical therapy for bone defects.